Single-port laparoscopy-assisted trans-scrotal hernia sac ligation for pediatric male inguinal hernia - Hang, Tian; Ma, Qichao; Hong, Zhihua; Wang, Jianfeng; Ling, Zhicai; Lin, Houwei (Frontiers in Surgery, 2022)
Objective: Introduction of a novel single-port laparoscopic-assisted transcrotal hernia sac ligation (LAT-HSL) technique for the treatment of inguinal hernias in pediatric males. In this article, we describe the LAT-HSL technique and the outcomes. Methods: Twenty-five male children with confirmed unilateral inguinal hernia who underwent surgical treatment from January 2020 to September 2021 were selected for this study. All children underwent surgical treatment with LAT-HSL, and the operative time, hospital stay, and postoperative results and complications were recorded. Results: All 25 cases underwent LAT-HSL with minimal perioperative complications, and all children were successfully discharged from the hospital postoperatively. At the postoperative follow-up, there was no retraction or atrophy of the testes, no incisional infection, no chronic pain, no urinary retention, and no recurrent hernias. Conclusion: Single-port LAT-HSL allows for rapid and accurate localization of the extra-abdominal hernia sac. The method is safe, easy to perform, and adaptable. Additionally, the scar is hidden, and the operation time is short.